Kedudukan Ruislagh Dalam Investasi Tanah Wakaf Perspektif Maqasid Syari’ah - Muhammad Ramli; Deni Setiyawan; Noor Rahmad (JATIJAJAR LAW REVIEW, 2022)
Wakqf is part of the teachings of Islam which aims to realize the general welfare. Seeing the reality on the ground, sometimes the waqf property is not in accordance with the purpose of the waqf, even ironically the waqf property is neglected. Seeing this phenomenon as Nadzir who is mandated to manage waqf assets, he must provide concrete and maslahah solutions. Not a few ruislagh become the final solution for waqf assets that no longer provide benefits. This study aims to describe the position of ruislagh in waqf land investment with a maqasid sharia perspective. The concentration of this research discusses the legal basis of ruislagh from the perspective of maqasid sharia and the position of ruislagh as a form of innovation in legal reform in the field of waqf. This study uses a normative method with a normative juridical approach. The results obtained: First, the legal basis of waqf in Indonesia refers to maqasid sharia. The two ruislaghs, apart from being legal, are also a way of renewing waqf management for the benefit of the people.